The construction of Algerian television advertisements and their impact on consumer behavior -A descriptive analytical study based on a sample of consumers- - Ahmad, Djilali; Attia, Hadj Salem (Journal of Ecohumanism, 2026)
This study examines the construction of television advertisements in Algeria regarding form, content, and their alignment with the cultural and social characteristics of Algerian society. It also evaluates their impact on consumer behavior and audience engagement. The findings reveal significant gaps stemming from weak regulatory frameworks and a lack of adaptation to digital advancements and creative demands. Based on these results, the study offers recommendations to improve advertisement quality and marketing effectiveness, aligning with local consumer needs while enhancing academic knowledge.